MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price:

There are no items in this cart.
Continue Shopping
                   

Is it right... To say.... dy/dx = dx/dy

3 years ago

Share

Answers : (7)

                                        

No this is incorrect.


(dy/dx) is actually equal to (dx/dy)-1

3 years ago
                                        

dy/dx=1/(dx/dy)

3 years ago
                                        

No,dy/dx=1/(dx/dy)

3 years ago
                                        

i dont know

3 years ago
                                        

acctualy dy/dx=1/dx/dy


 

2 years ago
                                        

no

2 years ago
                                        

never


dy\dx is change of y w.r.t x


but dx\dy is change of x w.r.t y which will turn out to be inverse of each other

one year ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
what is (x+3)(x -2)??
 
 
Hello Student, Please find the answer to your question (x + 3)(x – 2) = x^2+x-6 Hope that you will be satisfied with this
  img
Pankaj 9 months ago
 
absolutely correct. x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you both have understood now
  img
Pankaj 9 months ago
 
(x + 3)(x – 2) =x(x – 2) + 3(x – 2) = x^2 – 2x + 3x – 6 = X^2 + x – 6 Hope that you will understand now
  img
Pankaj 9 months ago
a 2 +9b 2 +25c 2 =abc((15/a)+(5/b)+(3/c)),then a,b,c are in a.A.P b.G.P c.H.P d. non of these
 
 
a 2 +9b 2 +25c 2 = 15bc+5ac+3ab a 2 + 9b 2 +25c 2 -15bc-5ac-3ab=0 multyply by 2 2a 2 +18b 2 +50c 2 -30bc-10ac-6ab=0 a 2 -6ab +9b 2 +9b 2 -30bc+25c 2 + 25c 2 -10ac +a 2 =0 (a-3b) 2 +(3b-5c) 2...
 
rajat Bansal 11 days ago
 
Let x=a,y=3b,z=5c So the expression reduces to x 2 +y 2 +z 2 =xy+yz+zx So (x-y) 2 +(y-z) 2 +(z-x) 2 =0 So x=y=z So a=3b=5c=r(say) So, a=r, b=r/3, c=r/5 which shows a,b,c are in HP (Ans.)
 
RAJORSHI PAUL 11 days ago
What is the value of 0 ∫ π/4 (cos 2x) 11/2 cosxdx ? (0 is lower limit and π/4 is upper limit)
 
 
|1/13*sin 2x^13/2| limit 0 to pie/4 1/13
 
Neha 3 months ago
 
|1/13*sin 2x^13/2| limit 0 to pie/4 1/13
 
Neha 3 months ago
 
|1/13*sin 2x^13/2| limit 0 to pie/4 1/13
 
Neha 3 months ago
if G is centroid of triangleABC and if G1 be the centroid of another trianglePQR show that AP(vector)+BQ(vector)+CR(vector)=3(G)(G1)
 
 
The capital letters denote the position vectors of the points: G = A + B + C/3 G1 = P + Q + R/3 3(G-G1) = A-P + B - Q + C - R 3GG1 = AP + BQ + CR Thanks Bharat Bajaj askiitians faculty IIT...
  img
bharat bajaj one year ago
 
The capital letters denote the position vectors of the points: G = A + B + C/3 G1 = P + Q + R/3 3(G-G1) = A-P + B - Q + C - R 3GG1 = AP + BQ + CR Thanks Bharat Bajaj
  img
bharat bajaj one year ago
A rop of length l slides with it’s ends on co-ordinates axis. Find the locus of it’s midpoint.
 
 
see, if (a,b)are the x n y axes,a 2 +b 2 =l 2 .....(c,d) midpt....c=a/2,,d=a/2....c^2+d^2=l^2/4....x^2+y^2=l 2 /4
 
RITABRATA SANYAL 8 months ago
View all Questions »